Clinical, Pathological, and Molecular Characterization of Infant Medulloblastomas Treated with Sequential High‐Dose Chemotherapy. Issue 9 (4th May 2016) - Lafay‐Cousin, Lucie; Smith, Amy; Chi, Susan N.; Wells, Elizabeth; Madden, Jennifer; Margol, Ashley; Ramaswamy, Vijay; Finlay, Jonathan; Taylor, Michael D.; Dhall, Girish; Strother, Douglas; Kieran, Mark W.; et al.
Abstract : Background: High‐dose chemotherapy (HDC) strategies were developed to avoid unacceptable neurotoxicity associated with craniospinal irradiation in infants with embryonal brain tumors. However, the impact of molecular and pathological characterizations in such approaches and long‐term outcome have not been widely described in young children. Methods: We retrospectively collected information from seven North American institutions, on young children with medulloblastoma (MB) treated with sequential HDC, as per the CCG 99703 protocol. Data collection included clinical presentation, histology, molecular subgroup, irradiation, ototoxicity, and neurocognitive evaluations. Results: The cohort included 53 patients diagnosed at a median age of 24 months (2.9–63.2). Seventeen patients (32.1%) had nodular desmoplatic MB, all belonging to the sonic Hedgehog (SHH) subgroup, as did 30% of classic MB. The 5‐year progression‐free survival (PFS) and overall survival (OS) was 69.6% (±6·9%) and 76.1% (±6.5%), respectively. Seventeen (32.1%) patients received irradiation (nine adjuvant radiotherapy [RT]). Patients with SHH and group 3 MB had a 5‐year PFS of 86·2% (±7.4%) and 49·1% (±14%), respectively ( P = 0.03). The 5‐year PFS radiation free for group 3 MB was 46.4%. Patients with macroscopic metastasis (M2 and M3) had a worst survival. Fifteen (45.5%) patients had significant ototoxicity. Mean Full Scale Intellectual Quotient (FSIQ) for 24 survivors was 91.6 (range 52–119). Conclusions: This HDC strategy led to an encouraging OS while only 20% of the patients received adjuvant RT. SHH MB, irrespective of histological subgroup, had an excellent outcome. Such intensive therapy may not be needed for this subgroup. Patients with classic histology or group 3 had an encouraging PFS of 58% and 46.4%, respectively, in the absence of adjuvant RT. The neurocognitive profile of the survivors appears to be within the normal range.